Clinical and histopathological characteristics and survival analysis of 4594 Japanese patients with melanoma. (1st April 2019) - Fujisawa, Yasuhiro; Yoshikawa, Shusuke; Minagawa, Akane; Takenouchi, Tatsuya; Yokota, Kenji; Uchi, Hiroshi; Noma, Naoki; Nakamura, Yasuhiro; Asai, Jun; Kato, Junji; Fujiwara, Susumu; Fukushima, Satoshi; et al.
Abstract: Background: The incidence of melanoma among those of an Asian ethnicity is lower than in Caucasians; few large‐scale Asian studies that include follow‐up data have been reported. Objectives: To investigate the clinical characteristics of Japanese patients with melanoma and to evaluate the prognostic factors. Methods: Detailed patient information was collected from the database of Japanese Melanoma Study Group of the Japanese Skin Cancer Society. The American Joint Committee on Cancer seventh Edition system was used for TNM classification. The Kaplan‐Meier method and Cox proportional hazards model were used to estimate the impact of clinical and histological parameters on disease‐specific survival in patients with invasive melanoma. Results: In total, 4594 patients were included in this analysis. The most common clinical type was acral lentiginous melanoma (40.4%) followed by superficial spreading melanoma (20.5%), nodular melanoma (10.0%), mucosal melanoma (9.5%), and lentigo maligna melanoma (8.1%). The 5‐year disease‐specific survival for each stage was as follows: IA = 98.0%, IB = 93.9%, IIA = 94.8%, IIB = 82.4%, IIC = 71.8%, IIIA = 75.0%, IIIB = 61.3%, IIIC = 41.7%, and IV = 17.7%. Although multivariate analysis showed that clinical classifications were not associated with survival across all stages, acral type was an independent poor prognostic factor in stage IIIA. Conclusions: Our study revealed the characteristics of melanoma in the Japanese population. The 5‐year disease‐specific survival of each stage showed a similar trend to that of Caucasians. While clinical classification was not associated with survival in any stages, acral type was associated with poor survival in stage IIIA. Our result might indicate the aggressiveness of acral type in certain populations.